2020
DOI: 10.1111/ajt.16141
|View full text |Cite
|
Sign up to set email alerts
|

Should cyclosporine be useful in renal transplant recipients affected by SARS-CoV-2?

Abstract: Minimization of immunosuppression and administration of antiretrovirals have been recommended for kidney transplant recipients (KTRs) with coronavirus disease 2019 (COVID‐19). However, outcomes remain poor. Given the likely benefit of cyclosporine because of its antiviral and immunomodulatory effect, we have been using it as a strategy in KTRs diagnosed with severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). We studied 29 kidney transplant recipients (KTRs) who were admitted to our institution with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
58
0
5

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(65 citation statements)
references
References 30 publications
2
58
0
5
Order By: Relevance
“…11 , 12 In the largest multicentre series, Cravedi et al reported 32% mortality in 144 inpatients although it did not specify how many recovered to discharge, while Kates et al reported 28-day mortality as 18% from its dataset where 254/318 patients were hospitalised. 10 , 17 Of other studies from which inpatient mortality could be calculated, it was 7/39 patients (18%) in Lubetzky et al across New York, 22 6/29 patients (21%) in both Rodriguez-Cubillo et al in Madrid and Chen et al in New York City, 23 , 27 15/42 patients (36%) in Bossini et al in Brescia and 9/25 patients (36%) Mohamed et al in London. 20 , 25 …”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…11 , 12 In the largest multicentre series, Cravedi et al reported 32% mortality in 144 inpatients although it did not specify how many recovered to discharge, while Kates et al reported 28-day mortality as 18% from its dataset where 254/318 patients were hospitalised. 10 , 17 Of other studies from which inpatient mortality could be calculated, it was 7/39 patients (18%) in Lubetzky et al across New York, 22 6/29 patients (21%) in both Rodriguez-Cubillo et al in Madrid and Chen et al in New York City, 23 , 27 15/42 patients (36%) in Bossini et al in Brescia and 9/25 patients (36%) Mohamed et al in London. 20 , 25 …”
Section: Resultsmentioning
confidence: 94%
“…From left to right, quality items were starred black if they fulfilled pre-defined criteria: selection was starred on representativeness of patients with the exposure of interest (kidney transplant), selection of the non-exposed group, ascertainment of exposure, and demonstration that outcome of interest (death) was not present at start of the study; comparability was starred on the study controlling for the exposure of interest, and any additional factor; outcome was starred on how the outcome was assessed, whether follow-up was long enough for the outcome to occur, and whether loss to follow-up was adequate enough to be unlikely to introduce bias. Study design Selection Comparability Outcome Manganaro et al 16 Single-centre case series ☆☆★★ ☆☆ ☆☆☆ Boyarksy et al 18 Cross-sectional national survey ☆☆☆★ ☆☆ ☆☆☆ Pereira et al 21 Two-centre case series ★☆★★ ☆☆ ★☆☆ Sánchez-Álvarez et al 12 National registry cohort ★★☆★ ★☆ ☆★☆ Vistoli et al 19 Cross-sectional national survey ★☆☆★ ☆☆ ☆☆☆ Rodriguez-Cubillo et al 23 Single-centre case series ★☆★★ ☆☆ ★★★ Pascual et al 13 National registry case series ★☆★★ ☆☆ ★☆☆ Chen et al 27 Single-centre case series ★☆★★ ☆☆ ★★★ Mehta et al 28 Single-centre case series ★☆★★ ☆☆ ★★★ Bossini et al 25 Multi-centre case series ★☆★★ ☆☆ ★★★ Cravedi ...…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, its use may be limited by its toxicity. However, a small case series of kidney transplant recipients changed to or maintained on cyclosporine A during treatment for COVID-19 did not show evidence of harm [73].…”
Section: Cyclosporine Amentioning
confidence: 96%